Generative AI and critical thinking in higher education: Students’ narratives of cognitive offloading - Roy, Bijon Kumar; Jony, Md. Solaiman (Journal of Interdisciplinary Studies in Education, 2026)
The rapid integration of generative artificial intelligence (AI) in higher education has raised important questions about its impact on students’ critical thinking. This study aims to explore how higher education students perceive the impact of generative AI use on their critical thinking. A phenomenological qualitative design was employed in this study. Data were collected through semi-structured interviews with 12 university students in Bangladesh and analyzed using thematic analysis. The findings indicate that generative AI use is associated with superficial engagement with academic content, diminished self-regulation of cognitive effort, increasing reliance on AI-supported thinking, and heightened awareness of related cognitive risks and internal conflict.